The impact of a single stretching session on running performance and running economy: A scoping review - Konrad, A.; Mocnik, R.; Nakamura, M.; Sudi, K.; Tilp, M. (Frontiers in Physiology, 2021)
One determining factor for running performance is running economy (RE), which can be quantified as the steady-state oxygen consumption at a given running speed. Stretching is frequently applied in sports practice and has been widely investigated in recent years. However, the effect of stretching on RE and performance is not clear. Thus, the purpose of this scoping review is to investigate the effects of a single bout of stretching on RE and running performance in athletes (e.g., recreational and elites) and non-athletes. The online search was performed in PubMed, Scopus, and Web of Science databases. Only studies that explored the acute effects of stretching on RE (or similar variables) and/or running performance variables with healthy and adult participants, independent of activity level, were included in this review. Eleven studies met the inclusion criteria with a total of 44 parameters (14 performance-related/30 metabolic parameters) and 111 participants. Regardless of the stretching technique, there was an improvement both in performance variables (21.4%) and metabolic variables (13.3%) following an acute bout of stretching. However, detrimental effects in performance variables (28.5%) and metabolic variables (6.6%) were also reported, though the results were influenced by the stretching duration and technique. Although it was observed that a single static stretching exercise with a duration of up to 90 s per muscle group can lead to small improvements in RE (1.0%; 95% CI: -1.04 to 2.22), negative effects were reported in running performance (-1.4%; 95% CI: -3.07 to -0.17). It was also observed that a single bout of dynamic stretching only resulted in a negligible change in RE -0.79% (95% CI: -0.95 to 4.18) but a large increase in running performance (9.8%; 95% CI: -3.28 to 16.78), with an overall stretch duration (including all muscles) between 217 and 900 s. Therefore, if stretching is applied without additional warm-up, the results suggest applying dynamic stretching (for a short overall stretching duration of =220 s) rather than static stretching if the goal is to increase running performance. In general, only short static stretching durations of =60 s per muscle-tendon unit are advisable. One study reported that less flexible runners have greater benefits from stretching than athletes with normal flexibility. In addition, it can be suggested that less flexible runners should aim for an optimum amount of flexibility, which would likely result in a more economical run.